Case study as a means of evaluating the impact of early years leaders: Steps, paths and routes. (April 2018) - Hadfield, Mark; Jopling, Michael
Highlights: I The importane given to context in recent research means case study is increasingly important in developing analyses of leadership effects. Case studies will need to use theoretically inclusive notions of leadership and its dynamics with organizational contexts. Case study's role is to illustrate the nature of local causality by tracing leaders steps along improvement paths through their organisation. The emperical scope of leadership studies need to be reduced in order to accommodate more complex theoretical accounts of local causality. The study of leadership effects require the development of typologies of leadership and leadership dynamics that can inform case selection. Abstract: The paper argues that case study will need to play an increasingly important role in the evaluation of leadership development programmes as both formal and substantive theories of leadership place greater emphasis upon the role played by organizational context on leaders ability to bring about change. Prolonged engagement within a case study provides researchers with opportunities to capture the dynamics between leaders and their organisational contexts. However, adopting a case study approach is no substitute for inadequate theorization of the link between leadership approaches and leadership effects. The paper argues for the use of inclusive and expansive theoretical notions of leadership and its relationship to organisational context. The evaluation used to illustrate these arguments was based on a longitudinal multi-site case study methodology. The case studies ran over a three-year period and tracked the effect of 42 leaders on the quality of provision in some 30 early years settings. Both individual and collective theoires of leadership were used to trace leaders' steps, paths and routes to improvement. Three overlapping theoretical lenses were used to study the dynamics of these leaders interactions with a key aspect of their organisational contexts - the existing formal and informal leadership structures – and how these affected their attempts to improve the quality of provision of their settings. The analysis, and related findings, were tiered in order to provide progressively more detailed descriptions of the relationships between leaders' approaches and changes in their settings' quality of provision. Each layer of analysis operated with a causal logic that became gradually less general and linear and increasingly more 'local' and complex.